Quality of life in older adults benefitting from institutionalized care and support during the COVID-19 pandemic - Bobrowicz-Campos, E.; Justo-Henriques, S. (Sustainability in aging: Challenges and opportunities for an integrated society, 2025)
This observational mixed-method study aimed to evaluate quality of life in older adults who benefited from institutionalized care and support during the COVID-19 pandemic. The study was registered in ClinicalTrials.gov (NCT05379426) and approved by the Ethics Committee from the Health Science Research Unit: Nursing (Approval Number: P871_04_2022). Fifty-eight institutions (nursing homes, adult day centers, and home support services) got involved in the study, recruiting 878 potential participants. Of these, 858 met the eligibility criteria, and 845 completed the assessment procedures. Data were collected between June and July 2022, using sociodemographic and clinical questionnaires, and the Quality of Life in Alzheimer's Disease scale, Centre for Epidemiologic Studies Depression Scale, Geriatric Anxiety Inventory, Loneliness Scale, Mini-Mental State Examination and Frontal Assessment Battery. Additionally, a semi-structured interview was conducted on the difficulties experienced during the pandemic. The analyses undertaken separately for older adults residing in nursing homes (n = 612) and in the community (n = 233) showed low levels of overall well-being, and high levels of depression, anxiety, and loneliness. The study findings, discussed in the light of testimonies obtained through the interviews, allow for a better understanding of the experiences of older adults during the pandemic, and outlining responses to minimize the negative impact of these experiences.